PERUBAHAN SIKAP TURKI TERHADAP PERMOHONAN SWEDIA BERGABUNG DENGAN NATO 2022-2024 - Hanip Arizal Sidiq (Journal of International Relations Diponegoro, 2025)
The war between Russia and Ukraine has affected many aspects of the international community. One of them is related to the security of the country, especially Sweden. Sweden, which felt that the intensity of the war was increasing, finally sought security protection by applying to join NATO. However, Sweden's path to join NATO was not easy because there was a rejection from Turkey regarding Sweden's support for an organization that Turkey considers a terrorist organization, namely the PKK. However, after Sweden fulfilled Turkey's demands regarding Turkey's unrest, Turkey finally approved Sweden's application to join NATO. Based on this, this research is conducted to see what factors influence Turkey's policy change towards Sweden's application to join NATO. This research uses K.J Holsti's theory of foreign policy change and uses a qualitative descriptive method. The results of the study show that there are several factors that influence Turkey's foreign policy changes, these factors are divided into domestic factors and also external factors. Apart from these factors, how President Erdogan's view in responding to Sweden's request is also one thing that can strengthen the factors above.